Status of serum calcium and vitamin D: a comparative study between premenopausal and postmenopausal women - Dhungana, Arun; Man Tamang, Jagat; Pandeya, Arun; Dahal, Sunit; Bhandari, Dinesh (Journal of Chitwan Medical College, 2025)
Introduction: Nowadays, most of the postmenopausal women are experiencing deficiencies in calcium and vitamin D, which has led to an increased risk of osteoporotic fractures. Prompt estimation of serum calcium, phosphorus, vitamin D, and alkaline phosphatase (ALP) can aid in preventing complications and providing proper treatment. This study aims to compare serum calcium, phosphorus, vitamin D, and ALP levels in premenopausal and postmenopausal women. Method: This was a quantitative cross-sectional study conducted in orthopaedic department at Kathmandu Medical College between 01 July – 31 December 2024. Ethical clearance was taken from Institutional Review Committee. Using consecutive sampling, participants' serum samples were analysed for calcium, phosphorus, and ALP activity using an automated analyser, and vitamin D was analysed using chemiluminescence immunoassays (CLIA) methods. T-test, Anova, Pearson’s correlation and Multiple Linear Regression analysis were calculated using SPSS. Result: Out of 244 participants, Body mass index (24.08±1.51 kg/m2), (p<0.001) vitamin D (24.11±9.27 ng/ml), (p=0.039), phosphorus (3.58±0.78 mg/dl), (p=0.232) and ALP (90.81±26.48 IU/L), (p<0.001) were higher in postmenopausal women, while serum calcium (9.14±0.50 mg/dl), (p=0.009) level was higher in premenopausal women. Vitamin D shows an insignificant positive correlation with serum calcium and ALP, while a negative correlation with phosphorus. Conclusion: The study concludes that postmenopausal women had a higher BMI. A decline in serum calcium and a rise in ALP levels among postmenopausal women were observed, indicating bone turnover and bone loss. Regular assessment and supplementation of calcium and vitamin D may be necessary to support bone health and prevent bone-related complications.